1998
DOI: 10.1302/0301-620x.80b1.0800038
|View full text |Cite
|
Sign up to set email alerts
|

Function after subtotal scapulectomy for neoplasm of bone and soft tissue

Abstract: We describe the functional results in 14 patients (7 men, 7 women) after subtotal scapulectomy for primary bone and soft-tissue tumours at a specialist musculoskeletal oncology unit. Eight had chondrosarcomas, two Ewing's sarcomas, one aggressive fibromatosis and three soft-tissue sarcomas. The mean follow-up was 52 months (6 to 120). Analysis of residual symptoms and of range and strength of movement by physicians used the Musculoskeletal Tumour Society rating scale (MSTS). Physical disability was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 10 publications
(14 reference statements)
0
20
0
1
Order By: Relevance
“…As the glenohumeral joint is well preserved, the extremity function that is obtained is good. Gibbons et al [6] reported the mean MSTS score was 71.6% in 14 cases with partial scapulectomy and concluded that the rotator cuff could be removed without a severe functional deficit provided that the deltoid was reattached to the scapular remnant and the trapezius. Mayil Vahanan et al [7] also reported partial scapulectomy in eight cases and gave superior functional results to total scapulectomy.…”
Section: Discussionmentioning
confidence: 99%
“…As the glenohumeral joint is well preserved, the extremity function that is obtained is good. Gibbons et al [6] reported the mean MSTS score was 71.6% in 14 cases with partial scapulectomy and concluded that the rotator cuff could be removed without a severe functional deficit provided that the deltoid was reattached to the scapular remnant and the trapezius. Mayil Vahanan et al [7] also reported partial scapulectomy in eight cases and gave superior functional results to total scapulectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Retention of glenohumeral articulation is important for the function of the shoulder joint after scapulectomy [7]. Gibbons et al [7] Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the shoulder girdle, including the proximal humerus, the scapula and the clavicle, is the third most common site for tumours of bone and soft tissue tumours, primary tumours of the scapula still present a rare diagnosis [1][2][3][4]. Most common tumours involving the scapula are chondrosarcoma in adolescents and Ewing's sarcoma in children [3].…”
Section: Introductionmentioning
confidence: 99%